Negara Hukum Kesejahteraan di Batas Pantai: Paradoks Perlindungan Negara terhadap Masyarakat Pesisir di Tengah Perubahan Iklim - Baskoro, Aji (Jurnal Ilmu Kesejahteraan Sosial, 2024)
Climate change poses significant challenges to vulnerable coastal communities in Indonesia. As a welfare state, the Indonesian government is expected to safeguard these vulnerable groups through policies that promote their welfare and sustainable livelihoods. However, current policies create a paradox. This article explores this paradox: on the one hand, Indonesia adheres to the welfare state principle, which demands that all government actions be grounded in law, ensuring public safety and welfare. On the other hand, the policies focus on exploiting natural resources, exacerbating the vulnerabilities of coastal communities, particularly in the face of climate change. The article employs a normative method by utilizing data from various literature sources, such as legislation and policy documents. The analysis combines statute, socio-legal and conceptual approaches to address the issues at hand. Findings indicate that despite Indonesia's constitutional declaration as a welfare state, this is not reflected in its current policies. The enactment of the Job Creation Law and industrial downstream policies have disregarded local wisdom, worsening the environmental and social vulnerabilities of coastal communities. This contradiction suggests an urgent need for policy reforms that better align with the principles of a welfare state and climate justice. The study recommends more integrative and holistic policy reforms, emphasizing long-term welfare, environmental sustainability, and the active participation of coastal communities.